Strategi Pembelajaran Untuk Optimalisasi Hasil Belajar Peserta Didik Program Paket C di Homeschooling Kak Seto Surabaya - Larasati, Esa; Riyanto, Yatim (J+PLUS UNESA, 2023)
The purpose of this research is to find out the learning strategies that are applied to optimize the learning outcomes of Package C program students at Homeschooling Kak Seto Surabaya. This research uses a descriptive method with a qualitative approach. Data collection techniques used are in-depth interviews, participant observation and documentation. The data analysis technique used is an analytical technique according to the theory of Miles, Huberman and Saldana. The results showed that the learning strategies applied to Package C Program students used the CTL (Contextual Teaching and Learning) approach with cooperative learning models, discovery-inquiry, problem based learning and hybrid learning while the methods applied were lectures, discussions and assignments. The factors supporting the synergy between institutions, parents, the community and students, conducive conditions, adequate facilities and a positive response from students. There are two inhibiting factors, namely internal factors related to the ability of students to understand the subject matter and external factors from outside that hinder the implementation of learning strategies, namely signal or network conditions that are less stable.